The Potential of Hot Water Mudiak Sapan Thermophilic Bactery Consortium Formulation in Producing Xylanase Enzyme - Irdawati; Indrawani Matondang; Linda Advinda; Azwir Anhar; Yusrizal Y (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The xylanase enzyme has high commercial value in the industrial sector, including the food industry, animal feed, bleaching of pulp/pulp, lignocellulosic bioconversion as fuel, and in the food industry, namely the cheese, bread and meat industries, while in the non-food industry this can be used in detergents. Xylanase enzymes can be produced from microorganisms, one of which is thermophilic bacteria. Thermophilic bacteria are known to be able to produce thermostable enzymes and proteins that are heat resistant. Xylanase production in compatible bacterial consortia was higher than monoculture. The purpose of this study was to determine the bicultur consortium that has the potential to produce xylanase enzymes. This research is an experimental research. Enzyme activity testing used the Miller method with DNS (Dinitrosalycilic acid) reagent using a completely randomized design (CRD) with 3 repetitions. Data on the results of xylanase activity were analyzed by ANOVA test and DMRT follow-up test with a 5% significance level.The results of the thermophilic bacterial isolates in the consortium that have the potential to produce xylanase enzymes are MS18 & MSS15, MSS15, MS16 and MS18 & MS16.